Wetlands, agriculture and poverty reduction - McCartney, Matthew P.; Rebelo, Lisa-Maria; Senaratna Sellamuttu, Sonali; de Silva, Sanjiv (International Water Management Institute, 2010)
In many places, growing population, in conjunction with efforts to increase food security, is escalating pressure to expand agriculture within wetlands. The environmental impact of wetland agriculture can have profound social and economic repercussions for people dependent on ecosystem services other than those provided directly by agriculture. If wetlands are not used sustainably, the functions which support agriculture, as well as other food security and ecosystem services, are undermined. This report synthesizes findings from multidisciplinary studies conducted into sustainable wetland agriculture by IWMI and partners in Africa and Asia. It highlights the value of wetland agriculture for poverty reduction as well as the need for more systematic planning that takes into account trade-offs in the multiple services that wetlands provide.